Development Governance Policy the Kawasan Seribu Rumah Gadang (SRG) in Solok Selatan Regency - Mike Fitriani Fitriani; Ramadhani Yusran; Karjuni Dt. Maani; Zikri Alhadi (Science and Environmental Journal for Postgraduate, 2023)
This study analyzes empirically the governance policies for the development of the Kawasan Seribu Rumah Gadang (SRG) in Solok Selatan Regency. This study uses a qualitative descriptive method with the location of Koto Baru, Sungai Pagu. Data was collected through interviews and documentation. This research shows that governance policies have not had a positive impact on people's welfare. This is due to poor management of the revitalization of Rumah Gadang, Homestay, and improvement of supporting facilities. This study concludes that local governments have not succeeded in implementing SRG tourism development governance policies by the plans that have been set.